A state estimation method for wireless structural control systems. Issue 6 (15th August 2016) - Sun, Z.; Ou, G.; Dyke, S. J.; Lu, C.
Summary: Structural control systems based on wireless sensors offer a convenient, flexible and cost‐effective alternative to their wired counterparts. Although wireless control systems (WCSs) have several attractive features, some challenges do remain related to the persistent presence of network‐induced time delays, and potential for sensor data losses and in extreme cases, sensor failures. The consequences of these challenges should be investigated, and solutions should be developed to achieve highly effective and robust control systems. The availability of such solutions will also encourage the adoption of WCSs in real structures. Here, an estimator switching method intended to minimize the influence of potential faults is developed and validated for WCSs. In this method, the switching gains are pre‐calculated to enable real‐time implementation. The proposed method is verified through numerical simulations of a seismically excited, three‐story structure considering various sensor data loss and sensor failure scenarios. The robustness of this estimation method in the presence of measurement noise and modeling uncertainty is also investigated. In addition, the estimation switching method is incorporated into a closed‐loop WCS in experiment. The results demonstrate the effectiveness of the proposed state estimation method in mitigating the impact of sensor data loss and sensor failure. Copyright © 2016 John Wiley & Sons, Ltd.